2020
DOI: 10.1177/1756284820902878
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and tolerability of a ready-to-drink bowel preparation: subanalysis by age from a phase III, assessor-blinded study

Abstract: Background: The incidence and mortality of colorectal cancer (CRC) increase with age and, therefore, it is recommended that adults undergo regular CRC screening, ideally by colonoscopy, with some new guidelines recommending screening begin at 45 years. Effective bowel preparation is a critical step to a successful colonoscopy. Of concern is that older adults may have poorer quality of bowel preparation or reduced tolerability for the bowel preparation. Here, we performed a post hoc secondary analysis for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…43 In this study, there was no variation in bowel preparation based on age or gender. Some research have shown that being elderly is beneficial, 44,45 but in males they were related to inadequate preparation, including in people from the Middle East and Asia. 8 However, studies are carried out on either an inpatient or outpatient basis, and it is widely recognized that inpatient bowel preparation is associated with poor bowel preparation when compared with outpatient scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…43 In this study, there was no variation in bowel preparation based on age or gender. Some research have shown that being elderly is beneficial, 44,45 but in males they were related to inadequate preparation, including in people from the Middle East and Asia. 8 However, studies are carried out on either an inpatient or outpatient basis, and it is widely recognized that inpatient bowel preparation is associated with poor bowel preparation when compared with outpatient scenarios.…”
Section: Discussionmentioning
confidence: 99%